Evaluation of thermo-chemical conversion temperatures of cannabinoid acids in hemp (Cannabis sativa L.) biomass by pressurized liquid extraction - Kenneth J. Olejar; Chad A. Kinney (Journal of Cannabis Research, 2021)
Abstract Background Cannabinoids are increasingly becoming compounds of medical interest. However, cannabis plants only produce carboxylated cannabinoids. In order to access the purported medical benefits of these compounds, the carboxylic acid moiety must be removed. This process is typically performed by heating the plant material or extract; however, cannabinoids being thermolabile can readily degrade, evaporate, or convert to undesired metabolites. Pressurized liquid extraction (PLE) operates using a pseudo-closed system under pressure and temperature. While pressure is maintained at 11 MPa, temperature can be varied from ambient to 200 °C. Methods Temperatures were evaluated (80 to 160 °C) using PLE for the thermo-chemical conversion of cannabinoid acids utilizing water as the solvent in the first step of extraction with subsequent extraction with ethanol. Optimum temperatures were established for the conversion of 6 cannabinoid acids to their neutral cannabinoid forms. Cannabinoid acid conversion was monitored by HPLC. Results The use of PLE for thermo-chemical decarboxylation has resulted in a rapid decarboxylation process taking merely 6 min. The temperatures established here demonstrate statistically significant maxima and minima of cannabinoids and their parent cannabinoid acids. One-way ANOVA analysis shows where individual cannabinoids are statistically different, but the combination of the maxima and minima provides temperatures for optimum thermo-chemical conversion. CBC, CBD, CBDV, and CBG have an optimum temperature of conversion of 140 °C, while THC was 120 °C for 6 min. Discussion Decarboxylation of cannabinoid acids is necessary for conversion to the bioactive neutral form. The pseudo-closed chamber of the PLE makes this an ideal system to rapidly decarboxylate the cannabinoid acids due to pressure and temperature, while minimizing loss typically associated with conventional thermal-decarboxylation. This study established the optimum temperatures for thermo-chemical conversion of the cannabinoid acids in water and provides the groundwork for further development of the technology for industrial scale application.